2017
DOI: 10.1007/s12035-017-0406-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Distribution of Arylsulfatase B are Closely Associated with Neuron Death in SOD1 G93A Transgenic Mice

Abstract: The known proteins only explained the partial pathogenesis of amyotrophic lateral sclerosis (ALS). Therefore, this study aimed to search the novel proteins possibly involved in ALS. In this study, we analyzed the expression and distribution of the candidate protein arylsulfatase B (ARSB) in the different segments, anatomic regions, and neural cells of spinal cord at the different stages of the wild-type and [Cu/Zn] superoxide dismutase 1 (SOD1) G93A transgenic mice using the fluorescent immunohistochemistry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Although we could not ensure that all significantly up regulated and down regulated proteins can be confirmed. Our better results 69 , 72 should confirm that our studied method and results were confident. Our results provided an important preliminary data for further studying the role of protein abnormality in the pathogenesis of ALS.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although we could not ensure that all significantly up regulated and down regulated proteins can be confirmed. Our better results 69 , 72 should confirm that our studied method and results were confident. Our results provided an important preliminary data for further studying the role of protein abnormality in the pathogenesis of ALS.…”
Section: Discussionsupporting
confidence: 74%
“…In the further studies, we confirmed some significantly up regulated and down regulated proteins by immunofluorescence histochemistry and western blot in spinal cord, brain and SOD1 G93A transfected PC12 cell lines. Among them, partial results have been published 69 , 72 , which were enough to confirm the reliability of our studying method. Although we could not ensure that all significantly up regulated and down regulated proteins can be confirmed.…”
Section: Discussionmentioning
confidence: 74%
“…It is obvious that hnRNP G has various and complex functions. Our studied groups found that the hnRNP G protein in the spinal cord of TG(SOD1*G93A)1Gur (TG) mice was signi cantly reduced through the methods of proteomic analysis [27]. The purpose of this study is to further explore the possible roles and mechanisms of hnRNP G in the pathogenesis of ALS.…”
Section: Introductionmentioning
confidence: 95%
“…The cellular cytotoxicity of mutants and/or cytoplasmic dislocated TDP-43 and FUS might be caused by the following reasons: (1) the loss of normal nuclear function leads to the disorder of nuclear RNA processing; (2) obtains the additional cytoplasmic RNA binding activity; (3) the polymerization dependent toxicity [7,[20][21][22]. More and more evidences show that the neurotoxicity generates through various cellular pathways, such as the RNA mismatch and the transcription reduction of c9orf72 gene, the disorder of transport between nuclear and cytoplasm, the stress of nuclear protein and DNA damage [23][24][25][26][27]. The break of DNA strand is the most serious types of DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular cytotoxicity of mutants and/or cytoplasmic dislocated TDP-43 and FUS might be caused by the following reasons: (1) the loss of normal nuclear function leads to the disorder of nuclear RNA processing; (2) obtains the additional cytoplasmic RNA binding activity; (3) the polymerization dependent toxicity [7,[20][21][22]. More and more evidence show that neurotoxicity generates through various cellular pathways, such as the RNA mismatch and the transcription reduction of c9orf72 gene, the disorder of transport between nuclear and cytoplasm, the stress of nuclear protein and DNA damage [23][24][25][26][27]. The break of DNA strand is the most serious type of DNA damage.…”
Section: Introductionmentioning
confidence: 99%